REPRESENTING, OBJECTIFYING, AND FRAMING THE BODY AT LATE BRONZE AGE KNOSSOS1. (15th May 2013) - ADAMS, ELLEN
<x xml:space="preserve">Abstract</x> This paper explores how the human form is depicted, objectified and contextualized, in order to clarify the complex relationship between 'representation' and 'reality', and to investigate the various ways the body is bounded. Part one argues that objectification is not always a passive process, but that the body is deliberately presented to the world to be observed and evaluated. Part two focuses on the configuration of bodily boundaries, and how the body is framed, for example, by clothing, architecture and the mortuary context. The wealth and range of evidence (wall paintings, seals and sealings, figurines, stone vases and burials) render Knossos an excellent case study for this approach. This paper asks not who the Knossians were, in terms of identity and ethnicity, but rather how they wanted to be presented to the world and each other.